A morphology-based evaluation on block-scale solar potential for residential area in central China. (June 2021) - Tian, Jia; Xu, Shen
Highlights: The solar potential in different residential blocks is simulated. The influences of block morphological parameters on solar potential are varified. Four parameters that impact on the block solar potential more than 70% are verified. The facade PV capacity in high-rise and hybrid residential blocks is more than 66%. The average PV installation rate of roof, south and west facade is 96%, 32% and 39%. Abstract: Block-scale application of photovoltaic technology in city is becoming a viable solution for renewable energy utilization. Rapid urbanization process has made urban buildings have huge development potential for solar energy in China, especially in residential areas that occupy large parts of the city. However, the residential blocks in China show differences in the morphological layout and parameters, which means they have diverse potential for solar energy development. This paper studies the effect of quantified morphological parameters on solar potential for residential blocks in Wuhan, China. The distribution characteristics of solar potential in different block environments are discussed. Various strategies are evaluated in terms of the installation position and height of PV modules. The results showed that floor area ratio, building density, average building height and building interval have significant impact on solar potential for residential block, and their correlation can reach 75%, 71%, 78% and 72% respectively. The average PV installation ratio of roof, south facade and west facade can reach 96%, 32% and 39% respectively. The results of this paper not only provide a reference to the block-scale application of PV technology in urban environment, but also stimulate the implementation of photovoltaic policies on various residential blocks in China.